Tackling Capacity Fading in Vanadium Redox Flow Batteries with Amphoteric Polybenzimidazole/Nafion Bilayer Membranes. Issue 12 (22nd May 2019) - Oldenburg, Fabio J.; Nilsson, Elisabeth; Schmidt, Thomas J.; Gubler, Lorenz
Abstract: Vanadium flow batteries are among the most promising technologies for stationary energy storage applications if their cost of storage can be further decreased. Capacity fading resulting from imbalanced vanadium crossover is a key operating cost component. Herein, a new approach is reported to avoid this cost by balancing electrolyte transport with amphoteric bilayer Nafion/ meta ‐polybenzimidazole membranes. Within this system, the anion‐ and cation‐exchange capacity can be tuned in a straightforward manner by changing the thickness of the respective polymer layer to balance electrolyte transport for a given current density. At high current densities, a net migrative flux of vanadium directed towards the positive side is observed owing to the higher average charge of vanadium ions present at the negative side. The coulombic repulsion between the vanadium ions and the positive charges in the membrane counteracts this migrative transport and can reverse the direction of the net vanadium flux. For a technically relevant current density of 120 mA cm −2, a PBI thickness of 3–4 μm is required to balance the vanadium crossover and to minimize capacity fading. Abstract : Minimized battery capacity fading : Amphoteric polybenzimidazole/Nafion bilayer membranes are proposed to minimize capacity fading in the vanadium flow battery. The bilayer membrane with varying thickness can be used to tune the net transport of vanadium from the negative to the positive electrolyte across the ion‐exchange membrane during charge–discharge cycling.